(3GdefM GdQMeGfjI aj GdOhdI GdYKeGfjIs - (3eMeO Hf eMeO GdHcQj GdUOjbi GdeYQha HGHf CHi GdSQhQ GdHcQi,J (B1087 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jefM ef TGA ef YHGOg aVdkG LRjdkG hGHJOCg HPcQ GdSdWGf YKeGf GdZGRi s
(3BNQgG (B:s
(3hNJeg HPcQ GdSdWGf eUWai s
(3hgh GdJGQjN GdUZjQ dgs
(3hbO Cdag hQJHg Ydi NeSI YTQ HGHkG HYO edhc gPg GdOhdI hPcQ YbH cd edc aVdG ajef Jhdi eUQ ef GdHcdQjcjI hgfGc Tcc ai Cf GdfGSN gheDdagGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B293s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B162 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs